Ari arranges everything - Vernon, Katie (Running Press Kids, 2023)
"For as long as anyone can remember, Ari has loved arranging things. From blocks to flowers to produce to unicorn toys, each arrangement feels perfect--though maybe not for everyone. But when Ari sets out to create the ultimate arrangement at the zoo, things don't go quite as planned."--